(untitled) (Journal of Hama University, 2024)
Small drones are exposed to many risks that affect reliability and safety as a result of technical problems occurring in one or more of their components, which leads to the aircraft failing to carry out its mission, losing it, or crashing into populated areas. The study aims to evaluate the risks of failure of components of a small drone on reliability and safety, based on the risk-based approach in accordance with the quality management system of the international standard AS9100D for aviation, space and defense sector institutions. Identifying high-risk failure patterns that could lead to catastrophic accidents using the Failure Mode and Effects Analysis (FMEA) approach, and arranging them according to the Risk Priority Number (RPN). And develop procedures to mitigate the risks resulting from the failure of partial systems of aircraft components by using components that are auxiliary to those systems